STRATEGI, MASALAH, DAN UPAYA MENYINERGIKAN DALAM PEMBELAJARAN IPS TERPADU PADA KELAS VIII SMP NEGERI 2 MAGELANG TAHUN AJARAN 2014/2015 - Aulia, Amna (Indonesian Journal of History Education, 2015)
The study was conducted at the eighth grade in junior high school 1 magelang with data collection using in-depth interviews, observation, and documentation. Validation data using triangulation techniques and triangulation of sources. Analysis of data using three interactive models, namely data reduction (data reduction), a data display (presentation of data), and verification (conclusion). The results showed that: (1) teachers to design learning strategies Integrated social science through the development of learning tools and technical preparation before the start of learning; (2) The internal problems that arise in the form of background learning teacher education is not education social studies and there are still students who are less concentrated in learning. While the external problem that arises is the lack of infrastructure as well as the most burdensome in the form of a new curriculum policy that mandated delivery of achievement of the students in the form of descriptive; (3) Efforts to synergize learning that teachers are training and fellowship meeting of teachers; schools also facilitate the needs of teachers and students. Â